PENGARUH KEPUASAN DAN WORD OF MOUTH TERHADAP LOYALITAS KONSUMEN PADA GREEN PRODUCT MEREK ORIFLAME DI KOTA DENPASAR - Ni Made Dewi Kansa Putri (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Consumers who are increasingly critical of global issues are primarily concerned with the environment, encouraging producers to market environmentally-based products. one of them through the use of the label